Detecting the Nation : Fictions of Detection and the Imperial Venture - Reitz, Caroline; Project Muse. (Columbus : Ohio State University Press, 2004)
In Detecting the Nation Reitz argues that detective fiction was essential both to public acceptance of the newly organized police force in early Victorian Britain and to acclimating the population to the larger venture of the British Empire. In doing so, Reitz challenges literary-historical assumptions that detective fiction is a minor domestic genre that reinforces a distinction between metropolitan center and imperial periphery. Rather, Reitz argues, nineteenth-century detective fiction helped transform the concept of an island kingdom into that of a sprawling empire; detective fiction placed imperialism at the center of English identity by recasting what had been the suspiciously un-English figure of the turn-of-the-century detective as the very embodiment of both English principles and imperial authority. She supports this claim through reading such masters of the genre as Godwin, Dickens, Collins, and Doyle in relation to narratives of crime and empire such as James Mill's History of British India, narratives about Thuggee, and selected writings of Kipling and Buchan. Reitz also shows how detective fiction and writings more specifically related to the imperial project, such as political tracts and adventure stories, were inextricably interrelated during this time. --Back cover.
Introduction : imperial detection -- Bad cop/good cop : Godwin, Mill, and the imperial origins of the English detective -- Thuggee and the "discovery" of the English detective -- Making an English virtue of necessity : Dickens and Collins bring it home -- Separated at birth : Doyle, Kipling, and the partition of English detective fiction -- Conclusion.
Description based on print version record.
Keywords: Roman anglais -- 19e siecle -- Histoire et critique; Imperialisme dans la litterature; Colonies dans la litterature; Police dans la litterature; Koloniale literatuur; Politie; Engels; Misdaadverhalen; Misdaadromans; Police in literature; Literature; Imperialism in literature; English fiction; Detective and mystery stories, English; Colonies in literature; British colonies; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Police in literature; Colonies in literature; Imperialism in literature; English fiction -- 19th century -- History and criticism; Detective and mystery stories, English -- History and criticism; Grande-Bretagne -- Colonies -- Dans la litterature; Great Britain -- Colonies -- In literature; Criticism, interpretation, etc; Electronic books